PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN SEKSUAL - Sistha, Windy Widya; Harahap, Irawan; Pardede, Rudi (LPPM STIH Awang Long, 2025)
Sexual harassment is regulated under Law Number 12 of 2022 concerning the Crime of Sexual Violence. Article 4 paragraph 2 of the law stipulates that anyone who commits non-physical actions such as gestures, writings, and/or words related to another person's body parts or sexual desires can be subject to criminal sanctions for non-physical sexual harassment. Offenders proven to have violated this law may face imprisonment of up to nine months and/or a maximum fine of IDR 10 million. The purpose of this research is to analyze the legal protection for victims of sexual violence based on the perspective of Law Number 12 of 2022 concerning the Crime of Sexual Violence, and to analyze the legal consequences of such protection. The method used is normative legal research. Based on the findings, the legal protection for victims of sexual violence under this law represents a significant milestone in Indonesia’s legal framework. The law progressively places the victim at the center of the legal process and broadens the definition of sexual violence beyond what was previously outlined in the Criminal Code (KUHP). Through this law, victims are granted broader rights, including legal assistance, rehabilitation, protection from intimidation, and recovery services. On the other hand, law enforcement officers have greater legal obligations to carry out investigations and trials with a victim-centered approach. The legal consequences of this protection not only affect the perpetrators in the form of criminal sanctions and additional penalties, but also impose institutional responsibilities on the state, including the provision of recovery services and reforming legal approaches. However, implementation challenges such as limited understanding among law enforcement, lack of support facilities, and low public legal literacy remain significant obstacles that must be addressed.